Combination of cord blood‐derived human hepatic progenitors and hepatogenic factors strongly improves recovery after acute liver injury in mice through modulation of the Wnt/β‐catenin signaling. (2nd May 2019) - Crema, Annalisa; Ledda, Mario; Fioretti, Daniela; Lolli, Maria Grazia; Sanchez, Massimo; Carico, Elisabetta; Marchese, Rodolfo; Rinaldi, Monica; Lisi, Antonella
Abstract: Cell therapy represents a promising alternative strategy for end‐stage liver disease, and hepatic progenitors are the best candidates. The possibility to maximize the paracrine effects of transplanted cells represents a great potential benefit for cell therapy success. We studied how cell type and microenvironment modulate the Wnt/β‐catenin signaling in vitro and in vivo. In vitro, the onset of hepatocyte commitment was characterized by the presence of nuclear truncated β‐catenin. In vivo, we analyzed the effect of human hepatic progenitors on damage recovery and functional regeneration in a mouse model of acute liver injury, either in combination or in absence of a selected mix of hepatogenic factors. Animals injected with human hepatic progenitors and hepatogenic factors showed improved engraftment triggering the Wnt/β‐catenin signaling cascade. Human hepatic progenitors expressing the human oval cell marker OV6 displayed a consistent colocalization with β‐catenin and colocalized with Wnt1 main ligand of the canonical pathway. Wnt5a, on the contrary, was expressed in distinct liver cell populations. Epithelial mesenchymal transition‐related markers showed enhanced expression and wider distribution, and the hepato‐mesenchymal population Thy1 + CK19− was also present. Control animals injected with hepatogenic factors alone exhibited higher β‐catenin, decreased Wnt5a levels, and persistent proliferation of the hepato‐mesenchymal population. In conclusion, the combination of human hepatic progenitors with selected hepatogenic factors creates a positive synergy with local microenvironment, ameliorates cell engraftment, stimulates and accelerates regenerative process, and improves the rescue of hepatic function by modulating the Wnt/βcatenin signaling and activating hepato‐mesenchymal population.